The Association Between Different Types of Dietary Carbohydrates and Colorectal Cancer: A Case-Control Study - Jonoush, Mona; Fathi, Soroor; Hassanpour Ardekanizadeh, Naeemeh; Khalatbari Mohseni, Golsa; Majidi, Nazanin; Keshavarz, Seyed Ali; Shekari, Soheila; Nemat Gorgani, Shiva; Torki, Saheb Abbas; Sotoudeh, Mahtab; Habibi, Fatemeh; Gholamalizadeh, Maryam; et al. (Frontiers in Nutrition, 2022)
Background: Multiple factors, including genetics, and environmental factors are involved in the development of CRC. A high intake of dietary carbohydrates may be potentially linked to an increased risk of CRC. This study aimed to investigate the association between different types of dietary carbohydrates and colorectal cancer. Methods: This hospital-based case–control study was carried out from June 2020 to May 2021 on 480 randomly selected participants (320 controls and 160 CRC patients, aged 35-70 years) in Firoozgar hospital, Tehran, Iran. Data on demographic and socioeconomic status, anthropometric measurements, dietary assessment, and physical activity was collected. Nutritionist IV software was used to determine the quantity of various forms of dietary carbohydrates including simple sugar, glucose, fructose, galactose, sucrose, lactose, and maltose. Results: The average daily consumption for calorie (2568.76±404 vs. 2493.38±176, P= 0.006) and carbohydrates (368.88±51.49 vs. 354.28±33.72 P< 0.001) were significantly higher among CRC cases compared to the controls. The logistic regression models of the association between CRC and dietary carbohydrates indicated that intake of carbohydrates (OR=1.009 CI95%:1.003-1.01, P=0.002), sugar (OR=1.02 CI95%:1.01-1.03, P<0.001), glucose (OR=1.06 CI95%:1.01-1.11, P=0.009), fructose (OR=1.31 CI95%:1.19-1.43, P<0.001), sucrose (OR=1.19 CI95%:1.12.-1.25, P<0.001), maltose (OR=9.03 CI95%:3.93-20.78, P<0.001), galactose (OR=1.31 CI95%:1.07-1.6, P=0.008) and lactose (OR=1.009 CI95%:1.01-1.18, P=0.02) were associated with CRC (All P< 0.05 in model 1). This relationship remained significant after adjusting for sex and age (model 2) and after additionally adjustment for sleep, tobacco, and alcohol level (model 3) and further adjustment for calorie intake and BMI (model 4). Conclusions: Patients with CRC had a significantly higher intake of calorie, carbohydrates, sugar, glucose, fructose, sucrose, and maltose. A positive association was found between CRC and dietary intake of carbohydrates, sugar, fructose, sucrose, and maltose. Future longitudinal studies are warranted to confirm these findings.